CIRC Learning Model for Reading Comprehension of French Language - Al Adawiyah, Aisyiah (Journal of Languages and Language Teaching, 2023)
Reading comprehension is a third language skill that must be mastered after speaking. What is expected of this skill is that learners can apply their understanding of the language to obtain information from reading. However, the reality found in the class shows that many learners complain about the difficulty of understanding sentences in a text, especially in the French language. This study aims to determine whether the CIRC model improves students' French reading comprehension before and after learning using the CIRC model. The use of the CIRC model for Reading Comprehension aims to improve the quality of students’ comprehension in obtaining French textual information. Its application to French reading comprehension is based on previous similar studies which state that this model is appropriate to be applied to improve reading comprehension skills. The research method of this study is a qualitative study with a classroom action research design. There were two cycles in this study, Cycle 1 was a research procedure before the CIRC model was applied and Cycle 2 was after the model was applied. Direct observations were made in the classroom during the RC learning process. Four learning steps that maximize individual abilities in group learning such as (1) the Planning phase, (2) the Implementation phase, (3) the Observation phase, and (4) the Reflection phase, produce a 5% increase in the value of the learning process. It is a certainty to apply this model for French reading comprehension to help learners understand a text well.